Relationship between antibodies to hepatitis C virus core+1 protein and treatment outcome - Mylopoulou, Theodora (Ann Gastroenterol, 2018)
BACKGROUND: It has been suggested that hepatitis C virus (HCV) core+1 protein plays a crucial role in the viral life cycle, potentially affecting liver cirrhosis and the development of hepatocellular carcinoma. METHODS: To investigate its relationship with the outcome of HCV standard combination therapy with peginterferon-α plus ribavirin, we screened 139 consecutive HCV patients (119 with chronic HCV infection and 20 who spontaneously cleared HCV) for the presence of anti-core+1 antibodies (Abs). In addition, liver fibrosis was determined by FibroScan in all but one patients. RESULTS: Twenty-nine patients were cirrhotic (stiffness >12.5 kPa, F4 METAVIR), all of them with mild liver cirrhosis (Child-Pugh score A). Eighty-six of 139 patients were treatment-experienced with standard combination therapy. Fifty of them had achieved a sustained virological response, while 36 were non-responders. The prevalence of anti-core+1 Abs in patients with chronic HCV infection was 22.69% (27/119 patients): 18% (9/50 patients) in responders and 36.11% (13/36 patients) in non-responders (P=0.050). Five (17.24%) of the 29 cirrhotic patients and 22 (24.72%) of the 89 non-cirrhotic patients were positive for anti-core+1 Abs (P=0.405). Furthermore, the presence of anti-core+1 Abs correlated with the poor response interleukin (IL) 28B genotype TT (P=0.040). No correlation between spontaneous clearance and anti-core+1 Abs was observed (P=0.088). CONCLUSION: The presence of anti-core+1 Abs might be correlated with the poor response IL28B TT genotype and may negatively affect the outcome of standard combination treatments in HCV patients, suggesting that core+1 may play a biological role in the course of HCV infection.